Effect of acupuncture on the sleep quality of hemodialysis patients in a capital city in the Northeast of Brazil - Geórgia Alcântara Alencar Melo; Marina Guerra Martins; Natália Ângela Oliveira Fontenele; Renan Alves Silva; Judith Sixsmith; Lívia Moreira Barros; Joselany Áfio Caetano (2024)
Objective: Analyze the effect of auricular acupuncture on the sleep quality of hemodialytic patients with chronic pain in a capital city in the Northeast of Brazil. Methods: This study includes double-blind, randomized in blocks and allocated at a rate of 1:1, controlled trial that was conducted in two hemodialysis clinics, with 94 chronic renal patients with chronic pain (auricular acupuncture [AA]: 47, sham acupuncture [SA]: 47). Both received 12 sessions for three months. We collected data using the Pittsburg Sleep Quality Index (PSQI). Data were analyzed using t-tests, Wilcoxon test and ANOVA. Results: Comparing the SA and AA groups, there was a statistically significant difference at baseline (p < 0.001), a significant intergroup difference, and the AA group had better sleep quality than the SA group during and at the end of the 12 sessions (< 0.001). A high magnitude of the effect of auricular acupuncture on sleep quality was found at the end of the sessions (D= -1.94). Conclusion: The auricular acupuncture intervention proved to be effective in improving the subjective sleep classification of renal patients.